An intervention to address math anxiety in the geosciences. Issue 1 (2nd January 2023) - M. Headley, Rachel
Abstract: Math anxiety involves moderate to extreme fear, anxiety, and occasionally physical pain associated with anticipating or performing mathematical tasks. High levels of math anxiety have been tied to students taking lower levels of math and choosing less quantitatively challenging courses and careers. In a small geoscience program in a primarily undergraduate university, math anxiety has been assessed using a standardized math anxiety rating survey embedded into a more general anxiety survey. An intervention that involves re-phrasing geoscience-focused quantitative word problems was used on both low- and high-stakes assessments. In courses with no intervention at both the major and general education levels, students were found to have similar math anxiety ratings and no significant change over the semester. In contrast, students in the intervention major courses were statistically more likely to have a drop in their math anxiety when compared to the large control and also when compared to a smaller control of similar-level courses. In a geoscience classroom, rephrasing quantitative questions to focus more on geoscience knowledge versus the quantitative task appears to be a viable way to lower math anxiety while giving students' experience to build their quantitative skills.